Microbial spectrum of urinary tract infections and its antibiogram in a tertiary care hospital - Yadav, Monika; Pal, Rohan; Damrolien, Shan; Khumanthem, Sulochana D. (International Journal of Research in Medical Sciences, 2017)
Background: Urinary tract infections are one of the major health problem effecting both sexes of all age group. UTIs are often treated with different broad-spectrum antibiotics. The aim of this study was to determine the prevalence of bacteria causing urinary tract infections and their susceptibility pattern from patients reporting in RIMS Hospital. Methods: Mid stream urine (MSU) specimens sent to the laboratory from October 2014 to September 2016 were collected and inoculated onto blood agar and MacConkey agar and incubated at 37ºC for 24 hours. Identification and antibiotic susceptibility test was done following standard operative procedures. Results: 25.66% (1142/4450) samples showed a significant growth out of which 42% (479/1142) were male and 58% (663/1142) were female. E. coli has been found to be the major pathogen causing UTI which account for 61% (696/1142) followed by Staphylococcus aureus 12% (137/1142), CONS 7% (79), Enterococcus spp. 6% (67), Klebsiella spp. 5% (57), Proteus spp. 2% (22), Pseudomonas spp. 2%, Acinetobacter spp. 2% and Candida spp. 3%. Imipenem was the most susceptible antibiotic for Enterobacteriaceae, E. coli (85.9%), Klebsiella spp. (89.4%) and Proteus spp. (95.4%). Vancomycin is 100% sensitive while Linezolid, Nitrofurantoin and Gentamicin are also highly sensitive for both Staphylococcus aureus and CONS. Conclusions: These data may be used to determine trends in antimicrobial susceptibilities, to formulate local antibiotic policies in order to assist clinicians in the rational choice of antibiotic therapy to prevent misuse, or overuse, of antibiotics.